Exploring 1,3,4-oxadiazole derivatives for hepatocellular carcinoma: synthesis, and bioactivity evaluation - Patidar, Mohini; Dubey , Raghvendra; Deshmukh, Nitin (Journal of Applied Pharmaceutical Research, 2025)
Background: Cancer is a leading cause of death globally, with existing treatments often limited by resistance and toxicity. This necessitates the development of new, more effective anticancer therapies. Methodology: This study used In-silico modeling with tools like Pre-ADMET and Molinspiration to evaluate the physicochemical, pharmacokinetic, and pharmacodynamic properties of substituted 1,3,4-Oxadiazole derivatives. Results and discussion: Computational studies of 1,3,4-Oxadiazole analogues showed promising drug-like properties and bioavailability. To test the inhibitory efficacy against the protein target tyrosine kinase (PDB: 1M17), 30 designed derivative compounds underwent molecular docking experiments. 10 synthesized derivatives were structurally confirmed through Mass, NMR, and IR spectrometry, ensuring their purity and identity.  Molecular docking and in vitro tests identified compound S23 as a potent tyrosine kinase inhibitor, with significant anti-proliferative activity (GI50: 0.25665634) and enzyme inhibition (IC50: 1.87), highlighting its potential as a therapeutic agent. Conclusion: According to our findings, the substituted derivative might offer superior potential for developing anticancer medicine.